Genetically Modified Sugarcane Intercropping Soybean Impact on Rhizosphere Bacterial Communities and Co-occurrence Patterns - Wei, Beilei; Zhang, Jinlian; Wen, Rushuang; Chen, Tingsu; Xia, Ningshao; Liu, Yue; Wang, Ziting (Frontiers in Microbiology, 2021)
Sugarcane is an important sugar crop with high nitrogen utilization efficiency. Strategies involving genes in the dehydration-responsive element binding (DREB) family, which participates in drought stress regulation, and intercropping with legumes are becoming prominent options in promoting sustainable sugarcane cultivation. An increasing number of studies focusing on root interactions in intercropping systems, particularly involving transgenic crops, are being conducted to better understand and thus, harness beneficial soil microbes to enhance plant growth. We designed experiments to investigate the characteristics of two intercropping patterns, soybean with wild-type (WT) sugarcane and soybean with genetically modified (GM) Ea-DREB2B-overexpressing sugarcane, to assess the response of the rhizosphere microbiota to the different cropping patterns. Bacterial diversity in the rhizosphere microbial community differed between the two intercropping pattens. The transgene in the GM sugarcane not only promoted the interspecific interaction between sugarcane and soybean but also enhanced the intraspecific competition between sugarcane plants. Furthermore, a beneficial rhizosphere environment for the growth of Actinobacteria was established in the systems intercropped with GM sugarcane. Improving the production mode of crops by genetic modification is a key strategy to improving crop yields and provides new opportunities to further investigate the effects of intercropping on plant roots and soil microbiota. Thus, this study provides a basis for selecting suitable sugarcane–soybean intercropping patterns and a theoretical foundation for a sustainable sugarcane production.